2020
DOI: 10.1128/msphere.00658-20
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Quantitative Real-Time PCR Assay for Monitoring SARS-CoV-2 Growth in Cell Culture

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has infected millions within just a few months, causing severe respiratory disease and mortality. Assays to monitor SARS-CoV-2 growth in vitro depend on time-consuming and costly RNA extraction steps, hampering progress in basic research and drug development efforts. Here, we developed a simplified quantitative real-time PCR assay that bypasses viral RNA extraction steps and can monitor SARS-CoV-2 growth from a small amount of cell culture supernatan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 10 publications
2
28
0
Order By: Relevance
“…To begin to decipher the mechanism(s) of SARS-CoV-2 entry into H522 cells, we performed infections in the presence of compounds that interfere with SARS-CoV-2 entry, including camostat mesylate (TMPRSS2 inhibitor) (Hoffmann et al, 2020; Shang et al, 2020; Shema Mugisha et al, 2020a), E64D (broad spectrum inhibitor of proteases, including endosomal cathepsins) (Ou et al, 2020; Shema Mugisha et al, 2020a), bafilomycin A (inhibitor of vATPase) (Ou et al, 2020; Shema Mugisha et al, 2020a) and apilimod (inhibitor of PIKfyve) (Kang et al, 2020; Ou et al, 2020; Shema Mugisha et al, 2020a). We additionally included a specific inhibitor of AAK1 kinase (SGC-AAK1-1); AAK1 promotes CME through phosphorylation of the AP2M1 subunit of the AP2 complex (Agajanian et al, 2019; Conner and Schmid, 2002, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…To begin to decipher the mechanism(s) of SARS-CoV-2 entry into H522 cells, we performed infections in the presence of compounds that interfere with SARS-CoV-2 entry, including camostat mesylate (TMPRSS2 inhibitor) (Hoffmann et al, 2020; Shang et al, 2020; Shema Mugisha et al, 2020a), E64D (broad spectrum inhibitor of proteases, including endosomal cathepsins) (Ou et al, 2020; Shema Mugisha et al, 2020a), bafilomycin A (inhibitor of vATPase) (Ou et al, 2020; Shema Mugisha et al, 2020a) and apilimod (inhibitor of PIKfyve) (Kang et al, 2020; Ou et al, 2020; Shema Mugisha et al, 2020a). We additionally included a specific inhibitor of AAK1 kinase (SGC-AAK1-1); AAK1 promotes CME through phosphorylation of the AP2M1 subunit of the AP2 complex (Agajanian et al, 2019; Conner and Schmid, 2002, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…To determine the antiviral activity and potency of the lead small molecules against SARS-CoV-2 we utilized a simplified Q-RT-PCR assay to monitor SARS-CoV-2 viral RNA levels in supernatants of infected Vero E6 cells. 32 Similar to Remdesivir, DMA-135 and 155 led to a dose dependent 10-30-fold decrease in cell-free viral RNA levels within 24 hours of infection with an approximate IC 50 of 10 and 16 μM, respectively ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 84%
“…Analysis of SARS-CoV-2 growth in cell culture supernatants was performed using a simplified RT-qPCR assay as explained before. 32 In brief, Vero E6 cells were infected with SARS-CoV-2 at an MOI of 0.1 i.u./cell in 96-well plates, virus inoculum was removed 1 hour post-adsorption and replaced with media containing serial dilutions of the DMA compounds. 5 μL of cell culture media containing released virions were collected at 24 hpi and processed as detailed in previous studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a large-scale drug repurposing study apilimod was responsible for blocking viral replication in human pneumocyte-like cells derived from induced pluripotent stem cells with IC 50 raging from 0.088 to 0.012 μM, as well as exhibited antiviral activity in a primary human lung explant model (Huang et al, 2020). Other study with Vero E6 cell viral replication monitored by QRT-PCR assays, indicated that apilimod potentially decreased the amount of SARS-CoV-2 RNA in cell culture supernatants, with an IC 50 of 12 mM and low cell toxicity (Shema Mugisha et al, 2020). Baloxavir marboxyl is an influenza A and B antiviral, which inhibits the cap-dependent endonuclease necessary for viral replication, and this is the first representative of influenza-type PB2 inhibitors.…”
Section: Discussionmentioning
confidence: 97%